Nassella trichotoma – plant growth rates and effects of timing of grubbing on populations in North Canterbury grassland. Issue 2 (3rd April 2019) - Bourdôt, Graeme W.; Saville, David J.
ABSTRACT: To quantify plant growth rates, responses to fertiliser and population responses to timing of grubbing (manual removal of plants) in a grassland population of Nassella trichotoma, three experiments were conducted. In Experiment 1, plant diameter growth, measured on 25 farms for up to 6 years, was unaffected by fertiliser and averaged 24 mm year −1, enabling a rapid increase in seed output. In Experiment 2, autumn and spring grubbing, compared on six 5-ha plots on four farms over six years, gave reductions in population size of 71% and 83%, respectively. In Experiment 3, effects of time of grubbing and pasture disturbance in spring/summer on recruitment were measured and combined with published demographic process rates in a simple population model. The model predicts population stability when 33.75% of plants are removed (the current mean grubbing rate) before mid-November with 3% pasture disturbance, and also for later grubbing with higher grubbing rate or lower pasture disturbance.